Intergenerational education and violence effects on adolescent education, early employment and adolescent parenting. (15th December 2022) - Mosha, Neema; Mshana, Gerry; Toska, Elona; Hertzog, Lucas; Desmond, Chris; Cluver, Lucie; Kapiga, Saidi; Stöckl, Heidi
ABSTRACT: Adolescence is a crucial phase in life, when foundations are established for future health . Therefore, supporting adolescents is necessary to meet the sustainable development goals by 2030. Evidence on the intergenerational transmission of poverty, education and violence suggests that to improve adolescents' well-being, the broader context in which they grow up needs to be understood when developing programmes and approaches to improve their lives. Our study explored intergenerational factors and early childhood influences on adolescent education, employment and parenthood, using the fourth wave of the MAISHA longitudinal study. This study took place in 2016–2021 among 986 adult women in Mwanza, Tanzania, including questions answered by the women on their adolescent's (aged 13–18) education, employment and parenthood, as well as their participation in early childhood programmes, education attainment and other socio-economic variables. Among the 577 mothers in our analysis who had adolescents living in their households, 32% reported that their adolescents did not attend secondary school, 11% were employed, 4% were pregnant or parents. For adolescents in secondary school, 15% ever failed a grade and 10% missed school more than 2 weeks in the last term. Grandparents' not having secondary education was significantly associated with adolescents not attending secondary education and being employed. Living in a female-headed household and mother's experience of intimate partner violence was associated with adolescent early employment. Early childhood influences showed no impact on any outcome in the multivariate analysis. Overall, we report a strong intergenerational impact of education on adolescent outcomes, suggesting the adoption of a strong policy focus on the provision of secondary education for both men and women due to its long-lasting effect. Interventions aimed at improving adolescent outcomes need to be long-term and invest in whole family poverty reduction measures.